The Role of Counseling in Increasing Stress Coping in HIV/AIDS Patients in Indramayu Regency - Evi Supriatun; Nafisah Itsna Hasni; Marsono Marsono (Program Studi DIII Rekam Medis dan Informasi Kesehatan, 2024)
This study aims to determine the effect of counseling on the stress coping of HIV/AIDS patients during antiretroviral treatment (ARV). Using a quasi-experimental design of one-group pretest-posttest, this study involved 30 respondents of adults diagnosed with HIV/AIDS. The results showed that counseling interventions significantly increased the use of problem-focused coping strategies and reduced emotion-focused strategies among respondents. The results of the analysis showed that counseling interventions had a significant influence on the coping strategies used by patients. The mean problem-focused coping score increased from 15.00 (SD = 3.50) before counseling to 25.00 (SD = 4.00) after the intervention, indicating a significant improvement in the use of more adaptive coping strategies. In contrast, the average emotion-focused coping score decreased from 22.00 (SD = 5.00) to 15.00 (SD = 4.50), indicating that counseling was effective in reducing the use of emotion-based strategies. Counseling has an important role in helping patients manage stress and motivate adherence to medication. This research is expected to contribute to the understanding and management of stress in people with HIV/AIDS through appropriate interventions.